Construção do conhecimento a partir das concepções espontâneas apresentado por alunos do ensino fundamental sobre o tema digestão - Forgiarini, Ana Maria Cera (2010)
At school today, teachers need not only to teach but also to be creative using educational resources to support teaching and especially to motivate students in the knowledge construction. The use of these resources must be appropriate with the purpose to help students learn. The report of experiences helps school teachers through alternative methods of education to bring together students from Science. This study aimed to check the student learning based on their spontaneous conceptions and help them to build the scientific knowledge about the theme proposed throughout the learning process. The study was carried out using questions and experimental activities. The topic chosen was digestion. Eight practical activities were done in order to diagnose the pre-existing knowledge of the students, which was then complemented with the scientific knowledge taught by the teacher aiming to motivate students to develop a taste for Science. This work was carried out with students from 6th to 9th grade of a public municipal school in Santa Maria, RS. The experiments performed at school were about the biochemical processes of digestion. All classes presented good performance in the practical classes, where a significant learning actually occurred according to the topic proposed. Our findings show that there was student enrichment in relation to the concepts taught, achieving a good understanding of the theme, i.e., the process of digestion. Although the students have demonstrated their understanding of the subject proposed, it is important to point out that they presented some difficulties to build the knowledge to new learning situations.